THE SOCIAL MEDIA AND SETTLED INDIANS: THE CASE OF KAINGANG AND KRENAK OF VANUÍRE VILLAGE IN ARCO - IRIS / SP (Fiep Bulletin - online, 2012)
Just as different cultures and especially the culture of white, indigenous highlighted, those who keep a close contact to city dwellers, also share the desire of the enjoyment of new technologies like the Internet. This desire can be achieved in the school environment, in the village itself or in visits to cities, houses specializing in the use of the Internet and in Internet cafes. The use of media is also in the design of the Indians as important institutions to disclose identity and visibility, as well as socialization, entertainment and knowledge that can be purchased with the systematic use of this tool, simply that the opportunity of contact between the involved, either in the school environment, or the collective individuality of their homes. In order to identify the relationship between indigenous teenagers and social media have been investigated 18 adolescents of the tribes and Kaingangs Krenaks Vanuíre village in the municipality of Rainbow / SP through a descriptive qualitative approach using a questionnaire open. The responses demonstrated in the construction of a new Indian that at some point should take advantage of existing technologies and specific needs, demystifying the picture that textbooks and much of the press have their information passed in the population. It was noticed yet, the interest of all involved that said they did not have the ability to access, at some point in order to access the network with the world and contact information.
Keywords: Social Media; Kaingang; Krenak